A comparative study of accounting standards : Singapore and the Philippines - Chan, Pei Wen (2013)
This study is carried out with the objective of obtaining a better understanding of the accounting practices in Singapore and the Philippines, which will contribute to better interpretation by investors of the accounting information prepared under the two accounting systems.